Prevalence of obesity and hypertension and its associated risk factors among chiru females of Manipur - Hosea Thanglen; Lorho Mary Maheo (Wolters Kluwer Medknow Publications, 2022)
Background: Obesity and hypertension are two well-known public health issues associated with a very high risk of cardiovascular diseases worldwide. It has become increasingly prevalent with the advancing chronological age and developing of noncommunicable diseases such as hypertension, diabetes, cancer, and respiratory diseases. Objectives: The paper aims to determine the prevalence of obesity and hypertension and their associated risk factors among the Chiru females of Manipur. Methods: A cross-sectional study was conducted among 207 Chiru females of Manipur, whose ages ranged from 20 to 79 years. Anthropometric and blood pressure were measured using standard procedures. Statistical methods such as Chi-square, Pearson correlation, and odds ratio (OR) were employed. Results: The nutritional status of the overweight and the obese are 33.3% and 11.6%. The overall prevalence of high blood pressure was 22.2%. This study observed a significant Pearson correlation between blood pressure and body mass index (BMI), age, physical activity, salt intake, smoking, and alcohol. The binary logistic regression, in terms of OR and coefficient of correlation, shows enough shreds of evidence that BMI and lifestyle factors are strongly associated and correlated with hypertension. Conclusion: The present study found a high prevalence of overweight and obesity among Chiru females, which might have contributed to the overall moderate prevalence of hypertension. Smoking, physical inactivity, and salt intake involve a significant risk of hypertension. Therefore, lifestyle has dramatically influenced the Chiru females of Manipur in terms of hypertension and obesity.